Psychology-Based Empathic Communication Model in Nursing: A Model to Enhance Patient Trust and Satisfaction - Yudhianto, Kresna Agung; Marni; Amin, Nur Azma (Bulletin of Counseling and Psychotherapy, 2025)
Effective communication between nurses and patients is essential in building therapeutic relationships, increasing patient trust, and enhancing satisfaction with healthcare services. This study employs a cross-sectional design to evaluate the impact of a psychology-based model of empathic communication in nursing on patient trust and satisfaction. The model, which emphasizes understanding, active listening, and emotional presence, is grounded in psychological principles that support patient-centered care. Data were collected through a structured survey administered to patients in healthcare settings in Indonesia and Malaysia. The study analyzes how empathic communication influences patient trust, reduces anxiety, and improves satisfaction with care. Findings indicate that implementing a structured empathic communication model significantly enhances nurse-patient interactions and contributes to better health outcomes. The results underscore the importance of integrating psychological principles into nursing communication practices to improve patient care quality.